If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.24(24) + 0.06x = 0.12(6 + x) Multiply 0.24 * 24 5.76 + 0.06x = 0.12(6 + x) 5.76 + 0.06x = (6 * 0.12 + x * 0.12) 5.76 + 0.06x = (0.72 + 0.12x) Solving 5.76 + 0.06x = 0.72 + 0.12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.12x' to each side of the equation. 5.76 + 0.06x + -0.12x = 0.72 + 0.12x + -0.12x Combine like terms: 0.06x + -0.12x = -0.06x 5.76 + -0.06x = 0.72 + 0.12x + -0.12x Combine like terms: 0.12x + -0.12x = 0.00 5.76 + -0.06x = 0.72 + 0.00 5.76 + -0.06x = 0.72 Add '-5.76' to each side of the equation. 5.76 + -5.76 + -0.06x = 0.72 + -5.76 Combine like terms: 5.76 + -5.76 = 0.00 0.00 + -0.06x = 0.72 + -5.76 -0.06x = 0.72 + -5.76 Combine like terms: 0.72 + -5.76 = -5.04 -0.06x = -5.04 Divide each side by '-0.06'. x = 84 Simplifying x = 84
| 2(m-8)+3=17 | | 8h+13h-6+7h-h+3g=0 | | -5x-9=6 | | -9=x+(19) | | x-22=6 | | 2(4t+1)=t+8+t-6 | | -3(4r+1)=33-6r | | -22+6x=-7(7+3x) | | 6-x-4=-1 | | 2(3t+1)=t+6+t-4 | | -r+3r=-2 | | -4=1-n-3 | | 2*(3t+1)=t+6+t-4 | | -9=n-6-4n | | 1+4b-5b=-2 | | -12v-9+7v=26 | | 5y+38=-2(y+9) | | 0=3b+b | | 6Y+3=3Y+11 | | 10x^2-x-1=0 | | -32=4x-8 | | (x+5)(x+13)=0 | | x^3=198 | | 6t-2t+2-2=2t-2t+2-2 | | 5b+2=2b+11 | | 180=x+(2x-18)+(x+30) | | 3x+4=12x+16 | | 180=(3x-30)+2x | | 230h=1265 | | 5a+4b-3a= | | -2(u-3)=-9u+27 | | 5y-8=-18 |